2019
DOI: 10.1021/acsami.9b06068
|View full text |Cite
|
Sign up to set email alerts
|

Nano-MOF+ Technique for Efficient Uranyl Remediation

Abstract: The nano-MOF+ technique was employed by assembling nanoporous metal-organic framework (MOF) UiO-66 with nanoscale zero-valent iron (ZVI) particles to remove uranyl ions from aqueous solution under anoxic condition for the first time. The synthesized composite of Fe0@UiO-66-COOH exhibits a synergic effect between uranyl sorption by MOF host of UiO-66-COOH and chemical reduction by ZVI, reaching much elevated removal capacity and rate in comparison to those of the pristine UiO-66-COOH. The combined complexation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 75 publications
3
17
0
Order By: Relevance
“…However, the performance of amorphous POPs is affected by its irregular pores, burying a large fraction of porosity 9 , and hindering fast mass transfer needed for real-time response 10 . Although MOFs have regular pores and good crystallinity 8 , stability under extreme conditions (acid, base, temperature, and radiation) remains a challenge [11][12][13] . High stability is particularly important for the extraction of UO 2 2+ , as the sample matrix is likely to be strongly radioactive and acidic.…”
mentioning
confidence: 99%
“…However, the performance of amorphous POPs is affected by its irregular pores, burying a large fraction of porosity 9 , and hindering fast mass transfer needed for real-time response 10 . Although MOFs have regular pores and good crystallinity 8 , stability under extreme conditions (acid, base, temperature, and radiation) remains a challenge [11][12][13] . High stability is particularly important for the extraction of UO 2 2+ , as the sample matrix is likely to be strongly radioactive and acidic.…”
mentioning
confidence: 99%
“…Wang et al reported a nZVI@UiO-66-COOH composite with nZVI assembled in the pores of UiO-66-COOH. [37] Compared with UiO-66-COOH, Fe 0 @UiO-66-COOH showed much faster adsorption kinetics with nearly 100 % removal of uranium in the first 10 min (Figure 8b). Furthermore, the uptake capacity of the composite for uranium was up to 504 mg/g, 7-fold that of UiO-66-COOH (Figure 8c).…”
Section: Uio-66-based Composite Adsorbents With Extra Active Sitesmentioning
confidence: 98%
“…Wang et al. reported a nZVI@UiO‐66‐COOH composite with nZVI assembled in the pores of UiO‐66‐COOH [37] . Compared with UiO‐66‐COOH, Fe 0 @UiO‐66‐COOH showed much faster adsorption kinetics with nearly 100 % removal of uranium in the first 10 min (Figure 8b).…”
Section: Uio‐66‐based Adsorbents For Uranium Recoverymentioning
confidence: 98%
See 2 more Smart Citations